Sulphur and sodium inputs from rainfall in relation to proximity of sites from the coast in peninsular Malaysia - Hussin, Aminuddin (Universiti Putra Malaysia Press, 1995)
Sulphur (S) and Sodium (Na)accessions through rainfall at sites of varying distances from the coast in Peninsular Malaysia were monitored. Result indicate that S accessions was of anthrophogenic and marine origin, with S deposition at site in the central and south transects being influenced more by industrial activities. Na accessions was related to the monsoons, with sites on the east coast having high accumulations during the northeast monsoon, and site on the west coast during the southwest monsoon. Na:S ratio was lower than their ratio in sea water indicating that S accession was from anthropogenic and terrestial origins.